Probing the rheological properties of supported thin polystyrene films by investigating the growth dynamics of wetting ridges. Issue 28 (29th June 2016) - Zuo, Biao; Tian, Houkuan; Liang, Yongfeng; Xu, Hao; Zhang, Wei; Zhang, Li; Wang, Xinping
Abstract : A facile method was developed to investigate the rheological behavior and dynamics of nanometer thick polymeric films by monitoring the growth of the "wetting ridge". Abstract : Despite its importance in the processing of nanomaterials, the rheological behavior of thin polymer films is poorly understood, partly due to the inherent measurement challenges. Herein, we have developed a facile method for investigating the rheological behavior of supported thin polymeric films by monitoring the growth of the "wetting ridge"—a microscopic protrusion on the film surface due to the capillary forces exerted by a drop of ionic liquid placed on the film surface. It was found that the growth dynamics of the wetting ridge and the behavior of polystyrene rheology are directly linked. Important rheological properties, such as the flow temperature ( T f ), viscosity ( η ), and terminal relaxation time ( τ 0 ) of thin polystyrene films, can be derived by studying the development of the height of the wetting ridge with time and the sample temperature. Rheological studies using the proposed approach for supported thin polystyrene (PS) films with thickness down to 20 nm demonstrate that the PS thin film exhibits facilitated flow, with reduced viscosity and lowered viscous temperature and a shortened rubbery plateau, when SiO x –Si was used as the substrate. However, sluggish flow was observed for the PS film supported by hydrogen-passivated silicon substrates (H–Si). The differences in enthalpic interactions between PS and the substrates are the reason for this divergence in the whole-chain mobility and flow ability of thin PS films deposited on SiO x –Si and H–Si surfaces. These results indicate that this approach could be a reliable rheological probe for supported thin polymeric films with different thicknesses and various substrates.